PENDIDIKAN AKHLAK DAN KENAKALAN REMAJA: STUDI PADA PESERTA DIDIK SMAN 1 CEPU - Armiya Nur Lailatul ‘Izzah (Jurnal Studi Islam dan Sosial, 2018)
This research is describing the role of Islamic Morals Education on the improvement of ethical guidelines for teens associating, the forms of ethical guidelines for teens associating, and the influence of Morals Education on guidelines for teens associating of students of SMA N 1 Cepu. The result shows that Islamic Education is used as guidelines in improving the ethical and moral in teens associating and reducing mischief of the students, and it is expected to form the personal piety and learner social godliness placed as a flagship program in forming the learner’s morality based on religious values understanding.The learning process uses meaningful learning strategies, means the delivering of learning materials put priority on its meaning, so that Islamic Education as a guide and moral values transformation. Islamic Morals Education has a significant influence in learner’s life either at school, in the family and in society; it is shown from the learner’s character such as: Trustworthiness, respect, diligence, responsibility, courage.